A Continuous Veno-Venous Hemofiltration Protocol with Anticoagulant Citrate Dextrose Formula a and a Calcium-Containing Replacement Fluid. Issue 6 (June 2014) - Ong, Song C.; Wille, Keith M.; Speer, Rajesh; Tolwani, Ashita J.
Introduction: Regional citrate anticoagulation (RCA) is used as an anticoagulant for continuous renal replacement therapy (CRRT). A systemic calcium (Ca 2+ ) infusion is required to replace Ca 2+ lost in the effluent. The shortage of intravenous Ca 2+ in the United States has limited RCA use. We describe a continuous veno-venous hemofiltration (CVVH) protocol with RCA using 2.2% anticoagulant citrate dextrose formula-A (ACD-A) and a commercial dialysate containing Ca 2+ 1.5 mmol/l (N × Stage) as post-filter replacement fluid (RF), without need for Ca 2+ infusion. Methods: We prospectively evaluated five patients on CRRT who had at least three episodes of filter clotting within 24 h. Patients were switched to CVVH using ACD-A infused pre-blood pump and titrated to achieve a post-filter ionized calcium (iCa 2+ ) level <0.5 mmol/l. The Ca 2+ -containing dialysate was delivered post-filter as RF. Results: Steady state mean serum chemistries were: Na + : 140.8 ± 2.3 meq/l, K + : 4.2 ± 0.4 meq/l, HCO3 – : 30.9 ± 3.7 meq/l, pH: 7.42 ± 0.07, CO2 : 47.9 ± 8.3 mmHg, total Ca 2+ : 8.08 ± 1.09 mg/dL. Post-filter iCa 2+ ranged 0.27-0.36 mmol/l, and patient iCa 2+ ranged 0.81-1.24 mmol/l. Mean post-filter RF rate: 3086 ± 164 ml/h, mean ACD-A rate: 298 ± 21 ml/h. Mean blood flow rate: 200 ± 17 ml/min, mean filtration fraction: 39.6 ± 7.2%. Mean effluent flow rate: 38.6 ± 6.7 ml/kg/h (range 28.7-55.8). Mean filter survival was 7 h without anticoagulation, compared to 42.6 h in the ACD-A group (p<0.0001). Conclusions: In this pilot study, CVVH using ACD-A for RCA and a Ca 2+ -containing RF was safely and effectively used without a continuous Ca 2+ infusion. This protocol is a promising solution for maintaining effective CRRT when intravenous calcium is in short supply.